An analysis of apology in an Indonesian ELT textbook and the teacher’s strategy to teach the apology - Waliyadin; Nurul Hayati Fauzi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
The apology is one of the speech acts that language functions cover. Considering that students must have pragmatic competence to use language appropriately in context, this research looked at apologies in an Indonesian senior high school ELT textbook, as well as the strategies used by teachers to teach apology. This study employed a qualitative approach which involves a textbook analysis and a semi-structured interview of the teacher’s teaching strategies to collect the data. The collected data then were classified, transferred into tables, and analyzed using Limberg (2015)’s principles of teaching pragmatics. The findings of this study show that the textbook entitled Bahasa Inggris Kelas XII covers some parts of Limberg’s principles of teaching pragmatics of apology. There is one principle that is not covered, namely, the principle of drawing a comparison. However, the findings of this study expose that the teacher’s teaching strategies cover all Limberg’s principles of teaching pragmatics of apology. Therefore, English teachers and institutions are expected to take into account the materials used to teach apology to students to raise students’ pragmatic competence.